Pengembangan Sistem Informasi Keuangan Operasional Masjid Ibnu Sina Malang menggunakan Metode Iteratif - Aldiransyah Rizky Putra; Ismiarta Aknuranda; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Ibnu Sina Mosque is one of the mosques located in the city of Malang. Just like mosques in general, the Ibnu Sina Mosque has a function as a place of worship, preaching, social activities, education and others. The Ibnu Sina Mosque is also a form of non-profit organization in which financial management is needed in implementing the operational functions of the organization. However, there are problems that occur when carrying out operational financial management in the Ibnu Sina Mosque. The data collection of financial reports that is still done manually means that the process of making reports takes quite a long time, then the data collection for spending on mosque needs is less recorded and inefficient, and the financial reports that are recorded are less detailed so that it risks causing misuse of funds. Based on the problems described earlier, a thesis project was carried out which aims to develop a web-based financial management information system that helps in conducting the operational finances of the Ibnu Sina Mosque. The method used in this development is the iterative method which produces two iterations. There is an outer iteration that focuses on problem analysis and needs analysis and an inner iteration that focuses on system design and implementation. This development is carried out using PHP programming language and the Laravel framework by applying an object-oriented approach. Then the system testing is carried out using validation testing methods and usability evaluation. The validation test results in all functions in both iterations being valid and usability evaluation results in a completion rate of 95.45% in the first iteration and 100% in the second iteration, the overall relative efficiency yields a value of 94,1% in the first iteration and 100% in the second iteration, and result in a SUS value of 70 in both iterations.